Single‐Face/All‐cis Arene Hydrogenation by a Supported Single‐Site d0 Organozirconium Catalyst. (17th March 2016) - Stalzer, Madelyn Marie; Nicholas, Christopher P.; Bhattacharyya, Alak; Motta, Alessandro; Delferro, Massimiliano; Marks, Tobin J.
Abstract: The single‐site supported organozirconium catalyst Cp*ZrBz2 /ZrS (Cp*=Me5 C5, Bz=benzyl, ZrS=sulfated zirconia) catalyzes the single‐face/all‐cis hydrogenation of a large series of alkylated and fused arene derivatives to the corresponding all‐cis‐cyclohexanes. Kinetic/mechanistic and DFT analysis argue that stereoselection involves rapid, sequential H2 delivery to a single catalyst‐bound arene face, versus any competing intramolecular arene π‐face interchange.